2007
DOI: 10.4314/eajph.v2i2.38960
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of measles in Tanzania: A hospital-based survey of measles morbidity and mortality

Abstract: Objective: To estimate measles morbidity and mortality in selected regions on mainland Tanzania Design: Cross-sectional study Setting: Hospital-based review of existing records on measles morbidity and mortality in the selected district hospitals on mainland Tanzania. Methods: Review of records on measles morbidity and mortality was performed using a standard instrument adopted from the Ministry of Health. The instrument was pre-tested before use. Researchers were recruited from the Muhimbili University Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In this study, it was observed that a high proportion of unvaccinated and partially vaccinated children (single dose) were laboratory confirmed to have measles. Similarly, a hospital-based study documented severe morbidity due to measles in unvaccinated individuals in Tanzania [28] . This can be explained by the fact that low vaccination coverage usually results in the accumulation of susceptible populations over time which can lead to outbreaks.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, it was observed that a high proportion of unvaccinated and partially vaccinated children (single dose) were laboratory confirmed to have measles. Similarly, a hospital-based study documented severe morbidity due to measles in unvaccinated individuals in Tanzania [28] . This can be explained by the fact that low vaccination coverage usually results in the accumulation of susceptible populations over time which can lead to outbreaks.…”
Section: Discussionmentioning
confidence: 98%
“…Despite Tanzania's limited financial resources, revaccination of individuals continues during measles outbreaks (Mnyika and Akim 2005). Routine measles vaccination for all children at 9 months was introduced in 1975 as part of its Expanded Program on Immunization (Mandara andRemme 1983, Goodson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…From 1995 to 2005, the responsible Ministry of Health ran annual mass immunization week campaigns involving all children under the age of five against all major childhood immunizable diseases including measles. In 2001, the age group eligibility for measles vaccination was extended to include children up to 15 years of age (Mnyika and Akim 2005). Measles first dose vaccination coverage increased from 46% in 198046% in to 80% in 199046% in , fluctuating between 72% and 83% through the 1990s, and increased from 78% in 200046% in to >90% in 200346% in -200746% in (WHO 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation